Neuroprotective effect of ranolazine improves behavioral discrepancies in a rat model of scopolamine-induced dementia - Samir, Shereen M.; Hassan, Hend M.; Elmowafy, Rasha; ElNashar, Eman Mohamed; Alghamdi, Mansour Abdullah; AlSheikh, Mona Hmoud; Al-Zahrani, Norah Saeed; Alasiri, Faten Mohammed; Elhadidy, Mona G. (Frontiers in Neuroscience, 2024)
Background Ranolazine (Rn), an antianginal agent, acts in the central nervous system and has been used as a potential treatment agent for pain and epileptic disorders. Alzheimer’s disease (AD) is one of the most prevalent neurodegenerative diseases and the leading factor in dementia in the elderly. Aim We examined the impact of Rn on scopolamine (Sco)-induced dementia in rats. Methods Thirty-two albino male rats were divided into four groups: control, Rn, Sco, and Rn + Sco. Results A significant decrease in the escape latency in the Morris water maze test after pre-treatment with Rn explained better learning and memory in rats. Additionally, Rn significantly upregulated the activities of the antioxidant enzymes in the treated group compared to the Sco group but substantially reduced acetylcholinesterase activity levels in the hippocampus. Moreover, Rn dramatically reduced interleukin-1 β (IL-1β) and IL-6 and upregulated the gene expression of brain-derived neurotrophic factor (BDNF). Furthermore, in the Sco group, the hippocampal tissue’s immunohistochemical reaction of Tau and glial factor activating protein (GFAP) was significantly increased in addition to the upregulation of the Caspase-3 gene expression, which was markedly improved by pre-treatment with Rn. The majority of pyramidal neurons had large vesicular nuclei with prominent nucleoli and appeared to be more or less normal, reflecting the all-beneficial effects of Rn when the hippocampal tissue was examined under a microscope. Conclusion Our findings indicated that Rn, through its antioxidative, anti-inflammatory, and anti-apoptotic effects, as well as the control of the expression of GFAP, BDNF, and Tau proteins, has a novel neuroprotective impact against scopolamine-induced dementia in rats.